The Relationship Between Self-Confidence and Emotional Stability and Shooting Accuracy in Football Among Students of the College of Physical Education and Sports Sciences University of Ai- Jafara - Abdel Fattah Al-Marghani Al-Mukhtar (Journal of Scientific and Human Dimensions, 2026)
The aim of this study was to identify the level of self-confidence and emotional stability in relation to shooting accuracy in football among students of the College of Physical Education and Sports Sciences. The researcher employed the descriptive method using the survey approach. The study population consisted of students of the College of Physical Education and Sports Sciences during the academic year 2022–2023, totaling 35 students. A random sample of 16 students was selected, representing 45.7% of the study population. To collect data and information, and based on reviewing previous studies that addressed some mental abilities and their relationship to shooting accuracy in football, the researcher prepared a questionnaire and a shooting accuracy test in football to achieve the objectives of the study. Appropriate statistical treatments were used to analyze the collected data. The study concluded several results, the most important of which were: higher self-confidence is associated with increased shooting accuracy; higher emotional stability contributes to reducing skill errors; and there is an integrative relationship between psychological and skill-related variables in the.